Spirulina platensis coating for the conservation of pomegranate - Luana Muniz de Oliveira; Ágda Malany Forte de Oliveira; Railene Hérica Carlos Rocha Araújo; George Alves Dias; Albert Einstein Mathias de Medeiros Teodósio; José Franciraldo de Lima; Luana da Silva Barbosa; Wellinghton Alves Guedes (AIMS Agriculture and Food, 2020)
The commercialization of fresh fruits among distant regions requires the adoption of storage technologies to ensure product preservation. This study evaluates the effect of Spirulina platensiscoatings on the conservation of pomegranates (Punicagranatum L.) and defines the best concentration for the coating of these fruits. The experiment was carried out in a completely randomized design with three replications and two fruits per replicate. Treatments consisted of different concentrations of Spirulina platensis (0%, 1%, 2%, 3%, and 4%) added with 0.5 mL L-1 of mineral oil. The fruits were stored at 24 ℃ and 60% RH, and evaluated after 15 days. The coating with 1% Spirulina platensis provided the best results, slowing color development, increasing brightness, maintaining sugars and ascorbic acid contents, and reducing astringency.